Pengembangan Perangkat Pembelajaran Model Advance Organizer Untuk Meningkatkan Hasil Belajar Fisika Peserta Didik - Putra, I Ketut Eka; Harjono, Ahmad; Hikmawati, Hikmawati; Gunada, I Wayan (Universitas Hamzanwadi, 2023)
This development research aims to produce a product in the form of a learning tool for the Advance Organizer model that is feasible, practical and effective to use to improve students' physics learning outcomes. The products produced in this development research include syllabus, lesson plans, worksheets and test instruments. The type of research conducted is Research and Development (R&D) with a 4D model design consisting of 4 stages, namely Define, Design, Develop and Disseminate. Data collection techniques used validation sheets, response questionnaire based and test sheets. The validation sheet is used to determine the validity of the learning device seen from the validation results by the validator. Response questionnaire sheets are used to determine the practicality of learning devices. The test sheet is used to determine the effectiveness of learning devices based on the pretest and posttest scores of students. The results obtained through data collection were 88.4% and 95.7% in the valid and reliable categories, 91.3% in the very practical category and 0.71 in the fairly effective category. Based on the data obtained, it can be concluded that the learning tools developed are valid, practical and effective to be used to improve students' physics learning outcomes.